The Effect Of The (SQ3R) Strategy Employing The Guided Discovery Method On Acquiring Passing And Shooting Skills In Football Among Students - Dahham, Nahidh Aboud (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Background and Study Aim. The study sought to examine the effect of the (SQ3R) strategy, implemented through the guided discovery technique, on students' acquisition of passing and shooting skills in football. Material and Methods. The researcher employed an experimental design featuring two equivalent groups with pre-test and post-test measures, chosen for its appropriateness to the research's nature. The researcher deliberately defined the research community as the fifth-grade literary students at Aleppo Boys' Preparatory School, comprising 105 students for the academic year 2023-2024, according to the fulfilment of research prerequisites. The researcher employed a basic random sampling approach through a lottery to choose the primary research sample, including 20 students, and subsequently divided it into two equal groups: one designated as the experimental group and the other as the control group. The researcher employed the statistical software (SPSS) to derive the research findings. Results. The study determined that the instructional units utilizing the (SQ3R) strategy in conjunction with the guided discovery technique positively influenced the acquisition of (passing - shooting) skills in football among the research sample. Conclusions. The study advocated for the implementation of the (SQ3R) technique alongside guided discovery to enhance the acquisition and mastery of football skills specifically, and sports skills broadly, for all genders.